Reflections of personality and loneliness on coping styles with stress in ındividuals engaged in recreational sport activities - ÖZCAN, BUŞRA (Acta Scientiae et Intellectus, 2025)
This study aims to examine the reflections of personality traits and loneliness on coping styles among individuals engaged in recreational sports activities. The sample consisted of 408 participants (207 females, 201 males) who completed the Ten-Item Personality Inventory, UCLA Loneliness Scale, and Coping with Stress Scale. Correlation and regression analyses revealed that loneliness was significantly predicted by specific coping styles, particularly the helpless and self-confident approaches. A strong positive relationship was found between the helpless approach and loneliness, while a moderate negative relationship emerged between the self-confident approach and loneliness. Seeking social support also showed a weak but significant positive correlation with loneliness. Among the personality traits, extraversion, emotional stability, and conscientiousness were positively associated with effective coping. The findings underscore the pivotal role of psychological resources and individual differences in managing stress and reducing loneliness in recreational sport contexts. The study suggests that enhancing self-efficacy and promoting active coping strategies can contribute to improved psychological well-being among recreationally active individuals.